'I'm not a doctor, but I can sew a mask': The face mask home sewing movement as a means of control during the COVID-19 pandemic of 2020. Issue 2 (1st September 2021) - Martindale, Addie K.; Armstead, Charity; McKinney, Ellen
As the COVID-19 pandemic emerged, a widespread shortage of personal protective equipment (PPE) specifically N95 face masks were exposed. This need was quickly answered by home sewers who did not hesitate to answer the request of medical professionals to help fill the PPE shortage. As the United States entered a national quarantine, home sewers turned to social media, specifically Instagram to share their participation and communicate the need to recruit others to join them in their mask sewing efforts. This research aimed to interpret the Instagram post messages shared to understand the motivations of participation in mask sewing efforts. Social media hashtags were used to identify the messages related to home sewing face masks for the pandemic. A netnographic qualitative research approach uncovered five overarching themes: this is helping me, call to action, do it right, rising to the occasion and I'm ready for this.